Physico-mechanical, chemical composition, thermal degradation and crystallinity of oil palm empty fruit bunch, kenaf and polypropylene fibres: a comparatives study - Noor Intan Saffinaz Anuar,; Sarani Zakaria,; Hatika Kaco,; Chia, Chin Hua; Wang, Chunhong; Husna Shazwani Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The physico-mechanical and chemical properties of enzyme retting kenaf and shredded empty fruit bunch of oil palm fibres (EFB) were analyzed by chemical extraction, microscopic, spectroscopic, thermal and X-ray diffraction method. Polypropylene (PP), a petroleum based fibre, was also included to compare the properties of synthetic fibre with natural fibres. Chemical extraction analysis showed that cellulose was the major component in both kenaf and EFB fibres which are 54% and 41.34%, respectively. Silica content of EFB was 5.29% higher than kenaf that was 2.21%. The result of thermogravimetric analysis showed that kenaf has higher thermal decomposition rate compared to EFB fibre. However, the residue for EFB fibre was higher than kenaf due to higher content in inorganic materials. The residual content of PP fibre was only 1.13% which was lower than the natural fibre. The diameter of EFB fibre bundle was 341.7 μm that was three times higher than kenaf. Microscopy study demonstrated that EFB surface was rough, porous and embedded with silica while kenaf showed smooth surface with small pith. Higher porosity in EFB was due to the lower fibre density that was 1.5 kg/cm3 compared to kenaf that was 1.62 kg/cm3. Kenaf has illustrated significant higher tensile strength (426.4 MPa) than EFB (150 MPa) and this result is in parallel to the pattern of the crystalline value for both fibres, 65% and 50.58%, respectively.